If it's not what You are looking for type in the equation solver your own equation and let us solve it.
13+2=-5(6x-3)
We simplify the equation to the form, which is simple to understand
13+2=-5(6x-3)
Reorder the terms in parentheses
13+2=+(-30x+15)
Remove unnecessary parentheses
+13+2=-30x+15
We move all terms containing x to the left and all other terms to the right.
+30x=+15-13-2
We simplify left and right side of the equation.
+30x=0
We divide both sides of the equation by 030 to get x.
x=0
| 36x+2=23x+1 | | -4.9t^2+27t+1=0 | | 8n+2n=134 | | 5(x-6)=3x | | 4(2x-1)=2(3x+6) | | .8=-.57 | | 18=7x+7x+4 | | 23x+1=36x+2 | | n-13=-10 | | 2(2x+4)=2x+24 | | n+33=50 | | 0.07x+4.59=4.73 | | 8y+4=3y | | 3=-3x+x+1 | | 7+2y=2y-2 | | 1/3(18y-6)=-5/8(12-6y) | | .75-.3z=.25 | | b-8+8b=18 | | 5x^2-2y+4=0 | | X+79=119+x | | 5(6x-2)-8=30x-18 | | 7x-3y=-20 | | 30=7x+5-2x | | 8(5d-9)= | | 9+1/4b=7 | | n-15= | | 9x+7=11x-7 | | 2.9=5.6-0.3x | | 7x-=-7 | | 4(9c+3)= | | 129x-19x=479 | | (3x-2)(5x-5)= |